Effects of modified pond management on limnological parameters in small‐scale aquaculture ponds in mountainous Northern Vietnam. (23rd April 2014) - Pucher, Johannes; Mayrhofer, Richard; El‐Matbouli, Mansour; Focken, Ulfert
Abstract: In mountainous Northern Vietnam, traditional pond aquaculture is part of the integrated farming activity contributing to food safety and to income generation for small‐scale farmers of ethnic minorities. Traditional pond management consists of a polyculture of macro‐herbivorous grass carp with 3–5 other fish species that are cultured in small ponds with constant water flow through. The main limitations to production are species‐specific mass mortalities of grass carp, a poor feed base especially for all species but grass carp, and poor water quality. In this study, we compared the traditional pond management to a semi‐intensive pond management that was based on the traditional management system but included changes designed by researchers to increase fish production. The modifications consisted of water inflow control, supplemental fertilization and feeding, and a polyculture dominated by common carp. The changes in management significantly reduced the turbidity and increased oxygen supply, as well as the natural food base within the pond. These changes in pond management provide farmers with the possibility to improve their pond aquaculture scheme and overcome previous limitations.